Model of Cultural Integration at Al-Hidayah Modern Islamic Boarding School, Jambi: Commitment to Building Multicultural Santri Character - Astuti Qomariyah, Khiqmah Ailmi (Cita konsultindo, 2025)
This study aims to explore the effectiveness of cultural integration programs in enhancing the tolerance attitudes of students at Pesantren Modern Al-Hidayah, Jambi. The program is designed to teach cultural diversity through interactive activities such as cultural festivals, intercultural dialogues, and active engagement with the surrounding community. The social issue underlying this research is the lack of effective interaction between students and the community, which can lead to misunderstandings and intolerant attitudes. Using a descriptive qualitative approach through a case study, the research involves students, educators, and the local community as primary respondents. Data were collected through in-depth interviews, direct observation, and documentation of cultural integration activities. The findings indicate that the program successfully enhances students' tolerance by fostering deep cross-cultural interaction experiences. Students reported improvements in communication skills, understanding of local cultural values, and conflict resolution abilities through dialogical approaches. Educators emphasized the importance of a multicultural curriculum supporting the program, while the community expressed a sense of greater harmony with the pesantren through active participation in joint activities. Thematic analysis identified key themes, such as changes in social attitudes, the program's role in fostering social cohesion, and implementation challenges involving cultural value differences. This study concludes that the cultural integration program at Ponpes Modern Al-Hidayah Jambi significantly strengthens tolerance and harmonizes relationships between students and the community. These findings contribute to the development of multicultural curricula in religious educational institutions and serve as a reference for enhancing the role of pesantren as centers for tolerance education in diverse societies.